INNOVATIVE APPROACHES TO ORGANIZATIONAL MANAGEMENT IN THE DIGITALIZATION ERA - MELNYK, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This article studies modern approaches to organizational management in the digitalization era. Its purpose is to analyse, systematize, and generalize these approaches. The research examines the transformation of organizational management under the influence of economic digitalization in the 21st century. An analysis of the main challenges traditional management models face amid the rapid development of digital technologies, including machine learning, artificial intelligence, big data, and the Internet of Things. The study substantiates the feasibility of shifting from hierarchical to adaptive management models that ensure flexibility, innovativeness, and rapid organizational adaptation to changes in the external environment. The concept of adaptive management as an open system that continuously adjusts its internal processes in response to market demands and technological changes is analyzed. The key factors for the successful functioning of adaptive management are identified: decentralization, delegation of authority, implementation of autonomous workgroups, and the active use of digital technologies for monitoring and analytics. The exploration of data-driven management features revealed its role as a strategic resource for decision-making, enhancing organizational flexibility, and creating added value. The importance of developing a data-driven organizational culture and implementing integrated information systems to establish evidence-based management practices is emphasized. The study also substantiates the role of digital-era leaders in shaping a vision of the digital future of organizations, promoting innovation, fostering a culture of continuous learning, and enhancing companies’ digital maturity. It is noted that effective leadership in the digital era is impossible without creating an atmosphere of trust, readiness for change, and the development of employees’ digital competencies. The article also analyses flexible management methodologies that have emerged in response to the challenges of the digital economy and have become essential tools for organizational adaptation to rapid environmental changes. Among the most widespread approaches, Agile, Scrum, and Lean are highlighted, which focus on iteration, flexible planning, constant interaction with stakeholders, and rapid response to new requirements. The research concludes that adaptive management, data-driven approaches, digital transformation leadership, and flexible methodologies are the key success factors for organizations in the digital economy. At the same time, modern management in the digital age requires a comprehensive approach that combines technological innovations, new leadership styles, a shift to open organizational models, and knowledge management.